Peranan Guru Dalam Membimbing Siswa Yang Melakukan Perilaku Bullying Di SD Negeri 3 Suak Lamatan Kabupaten Simeulue - Lauhil Maulindah; Mislinawati Mislinawati; M. Husin (Elementary Education Research, 2023)
The role of the teacher is as an organizer of the learning environment as well as a learning facilitator. This role requires that planning is always adapted to the conditions of the students, students' study habits, experience and knowledge of students, various learning methods and subject matter according to students' learning interests. The teacher does not only act as a provider of information to students but a complex action. Bullying behavior is caused by several factors, namely seniority, family, personality, school, social environment, television and print media, lack of self-confidence, wanting to be popular, and lack of empathy. The formulation of the problem in this research is "What is the teacher's role in guiding students who engage in bullying behavior at SD Negeri 3 Suak Latan, Simeulue Regency and what causes students to behave bullying at SD Negeri 3 Suak Latan, Simeulue Regency". This study aims to describe the teacher's role in guiding students who engage in bullying behavior at SD Negeri 3 Suak Latan, Simeulue Regency and what causes students to behave bullying at SD Negeri 3 Suak Latan, Simeulue Regency. The approach used in this research is a qualitative approach with a descriptive research type. This research was conducted at SD Negeri 3 Suak Lamatan, Simeulue Regency. with a subject of 25 students and 6 teachers. Data collection techniques in this study used observation and interviews. The data obtained was then analyzed based on student behavior, based on data analysis it can be interpreted that 2 people often engage in bullying behavior every week, 5 people behave moderately and 18 students behave well.